1985
DOI: 10.1159/000226061
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Treatment of Disseminated Male Breast Cancer

Abstract: 14 males with disseminated cancer of breast received a total of 35 endocrine trials, mainly in the form of hormonal supplementation. Overall, a 43% response rate was observed. In particular, remissions occurred in 7 of 11 instances with cyproterone acetate, in 3 of 7 with tamoxifen, in 2 of 5 with estrogens, in 2 of 5 with aminoglutethimide, in none of 3 with high-dose medroxyprogesterone acetate, in none of 1 with androgens, and in 1 of 3 with castration. The response to additive hormonal therapy was 44%. Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
6

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 10 publications
0
30
0
6
Order By: Relevance
“…One case series of three patients with advanced male breast cancer demonstrated partial remission in one patient and complete remission in the remaining two [27]. Other studies have found slightly lower success rates for males with advanced cancers, with 18% of patients showing complete response and 45% showing a partial response [26]. Other hormones with progestational activity have demonstrated mixed results.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One case series of three patients with advanced male breast cancer demonstrated partial remission in one patient and complete remission in the remaining two [27]. Other studies have found slightly lower success rates for males with advanced cancers, with 18% of patients showing complete response and 45% showing a partial response [26]. Other hormones with progestational activity have demonstrated mixed results.…”
Section: Discussionmentioning
confidence: 97%
“…Several reports exist showing mild to moderate success with a variety of agents. Estrogen therapy in the form of diethylstilboestrol has been shown to have a 38%-40% total response rate when given to patients with advanced or recurrent male breast cancer [25,26]. Cyproterone acetate, a synthetic steroid with antiandrogenic and progestational activity has also shown success.…”
Section: Discussionmentioning
confidence: 99%
“…Obwohl altersunabhängig Remissionsraten von 32-80% mit einer Dauer von 4-50 Monaten beschrieben sind [39,72,74,78,79], limitiert die psychologische Problematik dieser Maßnahme die generelle Akzeptanz. Allerdings ist auch nach Nichtansprechen ein weiterer hormoneller Therapieversuch in den meisten Fällen möglich [72,79,80]. Aminoglutethimid kann nach Orchidektomie bei sekundärem Therapieversagen noch zu Remissionen führen [81], aber auch alternativ vor der Orchidektomie eingesetzt werden.…”
Section: Systemische Adjuvanstherapieunclassified
“…Aminoglutethimid kann nach Orchidektomie bei sekundärem Therapieversagen noch zu Remissionen führen [81], aber auch alternativ vor der Orchidektomie eingesetzt werden. Während bei alleiniger Gabe über Remissionsraten von 9-45% mit einer Dauer von 3-12,5 Monaten [43,80] berichtet wurde, scheint nach Orchidektomie ein verbessertes Ansprechen möglich [81]. Trotz fehlender klinischer Daten ist der alternative Einsatz moderner hochspezifischer Aromatasehemmer der dritten Generation (Anastrozol, Letrozol, Vorozol) zu erwägen.…”
Section: Systemische Adjuvanstherapieunclassified
See 1 more Smart Citation